The influence of individual behavioral aspects toward audit judgment: the mediating role of self-efficacy - Pawitra, Dyah Ayu Kanina; Suhartini, Dwi (Universitas Hayam Wuruk Perbanas, 2019)
The financial statement should be relevant, reliable, and free of material misstatement to be valuable. To achieve this objective, it requires an independent auditor. This study aimed to examine the effect of the aspects of individual behavior consisting of knowledge, audit experience, pressure of obedience and complexity of tasks, and the psychological aspects of self-efficacy as a moderating variable to the auditor's audit judgment at Surabaya Public Accounting Firm. The data were taken by a questionnaire distributed to auditors in Surabaya Public Accounting Firm registered in the Directory of the Indonesian Institute of Certified Public Accountants 2017, with a minimum work period of 2 years (auditor partner). They were analyzed using SmartPLS 3.0. The results indicate that knowledge has a significant positive effect on audit judgment. On the contrary, the audit experience does not have a positive effect on audit judgment, and compliance pressure and task complexity do not negatively affect judgment audits. Self-efficacy, as a moderating variable, is only capable of moderating the pressure of compliance with judgment audits. This suggests that public accounting firms, as well as auditors, should increase their knowledge so that they can make better audit judgments.